2023
DOI: 10.1002/adma.202302248
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Enhanced Resonant Exciton‐Trion Conversion in Electrically Modulated Atomically Thin WS2 at Room Temperature

Abstract: Excitonic resonance in atomically thin semiconductors offers a favorite platform to study 2D nanophotonics in both classical and quantum regimes and promises potentials for highly tunable and ultra‐compact optical devices. The understanding of charge density dependent exciton‐trion conversion is the key for revealing the underlaying physics of optical tunability. Nevertheless, the insufficient and inefficient light‐matter interactions hinder the observation of trionic phenomenon and the development of excitoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…The performance of our SnSe 2 /MoS 2 PD could be further boosted by using a similar device configuration with a backside reflector, as it was shown in one of our recent works that such an optical cavity can greatly enhance the light matter interaction in WS 2 resulting a strong trion emission. [ 45 ] The results indicate the importance of utilizing unilateral depletion of the heterojunctions with large CBM offset to achieve high responsivity PDs. The SnSe 2 /MoS 2 heterojunction PD has a good photoresponse under zero bias with rise and fall times of 32 and 38 ms, respectively (Figure S4a, Supporting Information), due to the high built‐in potential at the n + ‐n junction.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of our SnSe 2 /MoS 2 PD could be further boosted by using a similar device configuration with a backside reflector, as it was shown in one of our recent works that such an optical cavity can greatly enhance the light matter interaction in WS 2 resulting a strong trion emission. [ 45 ] The results indicate the importance of utilizing unilateral depletion of the heterojunctions with large CBM offset to achieve high responsivity PDs. The SnSe 2 /MoS 2 heterojunction PD has a good photoresponse under zero bias with rise and fall times of 32 and 38 ms, respectively (Figure S4a, Supporting Information), due to the high built‐in potential at the n + ‐n junction.…”
Section: Resultsmentioning
confidence: 99%
“…Among various reports, [53][54][55] a direct absorption measurement estimated WS 2 trion binding energy around 31 to 37 meV at 5 K based on h-BN encapsulated samples, as shown in Figs. 2(b)-2(d), 56 and another study using reflectance contrast spectra reported the zero-density trion binding energy of 23 meV at 50 K. 57 Thanks to the cavity effect, Wang et al 58 recently determined the trion binding energy via the reflectance at RT to be around 42 meV in slightly n-doped condition, and they estimated the trion binding energy to be around 34 meV in the zero-density at zero bias by extrapolating the linearly fitted trion binding energies under different voltages, as shown in Figs. 2(e) and 2(f).…”
Section: Fundamentals Of Excitons In 2d Materialsmentioning
confidence: 97%
“…Very recently, the issue of insufficient light-matter interaction in trions that has impeded practical observation and application of trionic events has been investigated. 54 The study presents a solution utilizing an aluminum/alumina (Al∕Al 2 O 3 ) optical cavity, 58 as depicted in Fig. 4(e).…”
Section: Excitonic Tunability In 2d Materials For Active Metaopticsmentioning
confidence: 99%
“…32−34 To enhance the rate of exciton-to-trion conversion and improve the performance of trionic devices, plasmonic nanostructures are considered an ideal platform. 6,35,36 Plasmonic structures can induce hot electron generation, facilitate electron funneling, and reduce trion lifetimes, thus enhancing the functionality, selectivity, and sensitivity of such devices. 6,37,38 Here, we present a hybrid platform of a MoSe 2 monolayer (ML) on a plasmonic gold nanowire (AuNW) with a controllable Au tip, providing tip-enhanced cavity spectroscopy (TECS) for a 2D semiconductor.…”
mentioning
confidence: 99%
“…Recently, the phenomenon of exciton-to-trion conversion in 2D semiconductors has attracted significant attention. Trions offer distinct advantages over neutral excitons for optoelectronic device applications. Trions are responsive to external bias, enabling electrical control over their spatial distribution, a feature that can be harnessed in the development of trion-based integrated circuits. Additionally, trions have relatively shorter lifetimes and lower binding energies compared to excitons, making them conducive to the development of highly efficient photovoltaics, such as trion-based photocurrent devices and solar cells. To enhance the rate of exciton-to-trion conversion and improve the performance of trionic devices, plasmonic nanostructures are considered an ideal platform. ,, Plasmonic structures can induce hot electron generation, facilitate electron funneling, and reduce trion lifetimes, thus enhancing the functionality, selectivity, and sensitivity of such devices. ,, …”
mentioning
confidence: 99%